2005
DOI: 10.2527/2005.832301x
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian analysis of quantitative trait loci for boar taint in a Landrace outbred population1

Abstract: The genetic basis of the main components of boar taint was investigated in intact male pigs in a commercial population. We analyzed fat androsten-one and skatole concentrations from 217 males of an outbred Landrace population. Records were normalized using a logarithm transformation and tested for normality using a Wilk-Shapiro test. Bayesian analysis was then used to map QTL in 10 candidate regions previously selected on chromosomes 1, 2, 3, 4, 6, 7, 8, 9, 10, and 13. The criterion for QTL detection was the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
5
25
1
Order By: Relevance
“…A third study on boar taint QTL was carried out on a Landrace outbred population [48]. Androstenone and skatole concentrations in fat were determined in 217 intact boars.…”
Section: Detection Of Quantitative Trait Loci (Qtl)mentioning
confidence: 99%
See 1 more Smart Citation
“…A third study on boar taint QTL was carried out on a Landrace outbred population [48]. Androstenone and skatole concentrations in fat were determined in 217 intact boars.…”
Section: Detection Of Quantitative Trait Loci (Qtl)mentioning
confidence: 99%
“…In the literature, the average heritability value of androstenone levels is high (h 2 = 0.56), ranging from 0.25 to 0.88 [35] with recent estimated values in the same range [36,48]. Skatole levels show medium heritability values ranging from 0.19 to 0.54 [31,45].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the low resolution of these QTL studies, it is not possible to conclude whether they might be caused by the same genes segregating as in our study. The remaining boar taint QTL previously identified on SSC6 for smell intensity [39], subjective pork odour and skatole measurements [17,40] are located distal or proximal on SSC6. None of the other QTL studies investigating androstenone or sensory panel traits identified effects on SSC6 [19,24,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the slaughter weights were rather light at 80-85 kg live weight. A third study (Varona et al, 2005), designed to map QTLs in 10 candidate chromosomal regions identified from the previous studies, was carried out with a Landrace outbred population. These authors failed to detect any QTLs for androstenone in any of the candidate chromosome regions and instead detected a QTL for skatole on SSC 6.…”
Section: Genetic Effects On Boar Taintmentioning
confidence: 99%